2014
DOI: 10.7860/jcdr/2014/7256.3668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fast and Slow Pranayama Practice on Cognitive Functions in Healthy Volunteers

Abstract: Executive functions, PSS and reaction time improved significantly in both fast and slow pranayama groups, except reverse digit span, which showed an improvement only in fast pranayama group. In addition, percentage reduction in reaction time was significantly more in the fast pranayama group as compared to that in slow pranayama group. Both types of pranayamas are beneficial for cognitive functions, but fast pranayama has additional effects on executive function of manipulation in auditory working memory, cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Wei et al (2013) reported thicker cortex in Taichi chuan practitioners compared to control group: medial occipitotemporal sulcus, superior temporal gyrus and lingual sulcus in left hemisphere and the circular sulcus of the insula, precentral gyrus and middle frontal sulcus in right hemisphere. Furthermore, Gard et al (2014) showed that meditation may reduce cognitive decline associated with normal aging, and Sharma et al (2014) observed greater enhancement in cognitive domains such as memory retention and attention in yoga practitioners relative to controls. Gothe et al (2014) found that yoga practitioners had greater WM capacity compared with a control group that did stretching and strengthening exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al (2013) reported thicker cortex in Taichi chuan practitioners compared to control group: medial occipitotemporal sulcus, superior temporal gyrus and lingual sulcus in left hemisphere and the circular sulcus of the insula, precentral gyrus and middle frontal sulcus in right hemisphere. Furthermore, Gard et al (2014) showed that meditation may reduce cognitive decline associated with normal aging, and Sharma et al (2014) observed greater enhancement in cognitive domains such as memory retention and attention in yoga practitioners relative to controls. Gothe et al (2014) found that yoga practitioners had greater WM capacity compared with a control group that did stretching and strengthening exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Further, regulation of the speed-accuracy tradeoff within the three components of executive control might be the unifying mechanism through which yoga training is influential. Studies examining the effect of mindfulness-related practice on cognitive task performance report either speed (RT) or accuracy, but not both, as in the case with working memory tasks (e.g., Jella and Shannahoff-Khalsa, 1993;Jyothsna and Rao, 2014;Sharma et al, 2014;Johnson et al, 2015;Jansen et al, 2017;Purohit and Pradhan, 2017;Crivelli et al, 2018), planning and cognitive flexibility (e.g., Levine et al, 2011;Kiani et al, 2016), and inhibitory control (e.g., Lakey et al, 2007;Semple, 2010;Alfonso et al, 2011;Moore et al, 2012;Kiani et al, 2016;Wimmer et al, 2016). Results suggest that analyzing speedaccuracy tradeoff might be useful in exploring the unifying mechanism by which yoga and other mindfulness practices might enhance executive control.…”
Section: Discussionmentioning
confidence: 99%
“…Next, attention toward slowing paced movements improves postural control (Wu, 2002), and slow-paced breathing has the most evident cognitive benefits (Pal and Madanmohan, 2004;Jerath et al, 2006). However, some have found that both slow-and fast-paced breathing enhances cognitive control (Sharma et al, 2014). Slow movements during standing yoga postures require maintaining postural control against gravity; postural control failures pose a risk of losing body balance and falling.…”
Section: Introductionmentioning
confidence: 99%
“…Schranz & Osterode, 2009 [143]retest effects451042.131.141 2,29, 3.43Determination TestActioncomplex−0.52−1.02−1.29 1.141 2,29, 3.43Determination TestReactioncomplex−0.56−0.91−1.1033. Sharma et al, 2013 [144]intervention: passive CG46281912.00auditory reaction time test complex0.01 12.00Letter Cancellation Test complex−0.10 12.00Trail Making Test Apart Acomplex−0.17 …”
Section: Table A1mentioning
confidence: 99%